The Art of Performance : Palazzo Grassi Venice 8 - 12 August 1979. - Glusberg, Jorge; Battcock, Gregory; Berger, René; University New York (Buenos Aires : CAYC - Centro de Arte Y Comunicacion, 1979)
Agnetti, Vincenzo ; Clareboudt, Juan ; chiari, Giuseppe ; Fischer, Hervé ; Gerz, Jochen ; Haxton, David ; Joubert, Bernard ; Journiac, Michel ; Kahlen, Wolf ; Kaprow, Allan ; Kriesche, Richard ; Kubisch, Christian ; etc.
The Art of Performance, Palazzo Grassi Venice, Performances, August 8 - 12, 1979
Engels & Frans
boek